Unlooping the Loop - David Dowell (Oz, 2012)
While watching the Big 12 men’s basketball semi-finals on television a few weeks ago, I was gratified to see clips of downtown Kansas City, Missouri, filled with people. Amid the busy streets and shiny, occupied buildings, I could just make out the illuminated guardrail panels on a series of bridge rehabilitation projects completed within the past five years.